Assessing driving fitness in dementia: a challenge for old age psychiatrists. (October 2019) - Neilson, Duncan; Chacko, Emme; Cheung, Gary
Objective: To investigate how old age psychiatrists consider the fitness of dementia patients to drive safely and the challenges they face. Method: Participants were interviewed using a semi-structured approach that explored topics including their approach to driving fitness and cessation, challenges experienced and previous training. Thematic analysis was used to generate main themes. Results: Thirteen participants were recruited. Most felt they were not experts in driving fitness. Many found these assessments challenging for both themselves and their patients, with a negative impact on therapeutic alliance. There was a lack of formal training and variability both in the approach when considering fitness to drive as well as raising the issue of driving with patients. Conclusions: These results highlight the need to increase the availability of training for driving fitness, and to develop a standardised approach to help improve consistency amongst clinicians.